Neoadjuvant Treatment in Rectal Cancer - R., Srinath Bhradwaj; Sarin, Aditya; Aggarwal, Shyam; Halder, Shikha; Hukku, S.; Mustafa, Taha; Arora, Vijay; Malik, V.K.; Singh, Shivendra; Rao, G.V.; Saklani, Avinash; Bhojwani, Rajesh; Rawat, Saumitra; Selvasekar, C.; Parikh, Purvish M. (South Asian Journal of Cancer, 2024)
A major advance in rectal cancer was the evidence supporting short-course radiotherapy and long-course chemoradiotherapy. Both have been shown to improve local outcomes. Total neoadjuvant therapy (TNT) is the new kid on the block that provides further benefit of improving local responses as well as reducing systemic relapses, thus increasing overall survival. Details of the four key TNT trials are discussed. They pave the way for nonoperative management for patients who achieve clinical complete responses.
Keywords: TNT; NOM; LCCRT; SCRT